Horace M. Kallen in the Heartland The Midwestern Roots of American Pluralism - Steiner, Michael C. (Book collections on Project MUSE., 2020)
"While scholars regularly credit Horace M. Kallen for originating the concept of cultural pluralism-in which many cultures coexist within the dominant culture-they routinely ignore the Midwest's deep impact on his thinking. He is generally depicted as a dissatisfied Easterner who endured seven years of exile from 1911 until 1918 in a dreary hinterland. In contrast to this view, Steiner demonstrates that the Midwest was the essential catalyst for Kallen's theory. He traces the concept to its origins in the Midwest during the first decades of the twentieth century and recognizes the region as the source of an expansive idea that continues to reverberate a century later. Kallen's Midwest was a matrix of cultural pluralism, and Steiner connects the philosopher to the economic and cultural dynamics of his adopted region as well as to a wider pluralist community of thought that influenced him. Toward the close of the book, Steiner traces the similarities and differences between cultural pluralism and multiculturalism that emerged by the time of Kallen's death in the early 1970s and discusses the expansion and renewed relevance of his Midwestern-based theory into the twenty-first century"--